1992
DOI: 10.1152/jappl.1992.73.5.2192
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum enzyme activity: an explanation-based model

Abstract: The well-documented pattern of elevated serum enzyme activity (ESEA) data after a single bout of unaccustomed exercise can very easily be modeled using a biexponential curve. However, the changed pattern of ESEA after a second exercise bout, or after a period of conditioning or during repetitive training, demonstrates that exercise-induced adaptations have been taking place. The mechanism for this is unclear. One plausible explanatory hypothesis is that within the pool of muscle fibers, some fibers are stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is also possible that, if only a small percentage of the muscle fibres were damaged (for example, fast fibres), undamaged fibres could counterbalance the limited capacity of force production of the formers (Dedrick and Clarkson 1990). In fact, it has been suggested that a group of more fragile, stress susceptible fibres exists; these fibres would be reduced in number after a first bout of exercise, while the stronger fibres would survive (Morton and Carter 1992).…”
Section: Recovery Of Mechanical Neurophysiological and Blood Parametersmentioning
confidence: 99%
“…It is also possible that, if only a small percentage of the muscle fibres were damaged (for example, fast fibres), undamaged fibres could counterbalance the limited capacity of force production of the formers (Dedrick and Clarkson 1990). In fact, it has been suggested that a group of more fragile, stress susceptible fibres exists; these fibres would be reduced in number after a first bout of exercise, while the stronger fibres would survive (Morton and Carter 1992).…”
Section: Recovery Of Mechanical Neurophysiological and Blood Parametersmentioning
confidence: 99%
“…We investigated flight-induced muscle damage during migration by measuring plasma creatine kinase (CK) activity in two species of long-distance migrant shorebirds with very different migration strategies. Plasma CK activity is one of the most widely used indicators of exercise-induced skeletal muscle damage (Clarkson et al, 1992;Morton and Carter, 1992;Komulainen et al, 1995;Sorichter et al, 1997;Clarkson and Sayers, 1999), and its suitability for use in birds is based on a number of studies (Franson et al, 1985;Bollinger et al, 1989;Dabbert and Powell, 1993;George and John, 1993;Knuth and Chaplin, 1994;Totzke et al, 1999).…”
Section: A Sport-physiological Perspective On Bird Migration: Evidence For Flight-induced Muscle Damagementioning
confidence: 99%
“…Environmental variability inherently structures biological communities and is frequently observed in aquatic systems as hydrologic disturbances [ 1 ]. Flooding and drying of ephemeral habitats can affect aquatic invertebrate communities via direct mortality (e.g., [ 2 3 ]). Direct mortality and the resultant changes to the composition of communities from hydrologic changes have been relatively well-studied in ponds (e.g., [ 4 ]), streams (e.g., [ 1 ]), and some ephemeral container systems, such as water-filled tree holes (e.g., [ 5 ]).…”
Section: Introductionmentioning
confidence: 99%